Microfinance Usage And Living Standards In Kenya Microfinance Usage And Living Standards In Kenya - Kithinji, Beth (Graduate School of Business (GSB), 2024)
The establishment and operation of microfinance institutions have been aimed at reducing poverty. Even though the microfinance industry's strengths outnumber its disadvantages, the microfinance industry still faces major challenges in delivering its services. The general objective of the study is to investigate the effects that microfinance usage has on living standards in Kenya. The specific objective of focus included: To establish and determine the effect of micro-credit facilities and micro-saving facilities on living standards in Kenya. This study adopted the use of an explanatory research design. The population of this study comprised all microfinance institutions in Kenya, both unregulated and those regulated by the Central Bank of Kenya. The study used secondary data. Descriptive statistics were utilised to describe the patterns in the data, demographics analysis, and particularly, microfinance institutions (MFI) products and services usage. Linear regression analysis – ordinary least squares – is used to estimate the effects of access to MFI loans, amounts of MFI loans and savings in microfinance institutions by households on monthly household expenditures and household incomes. The effects of microfinance institutions on the household wealth index, which is ranked one to five, uses the multinomial logit model. Based on the descriptive findings, 65.6% of households interviewed are in rural areas. Fifty-eight percent of the heads of the households are male with 55% of the respondents being married or living with their partner. The average age of respondents was 39 years and the average size of each household/number of dependents is approximately two people. The majority of the household heads had only attained primary education level. It was found that 0.61% of all households held microfinance credit facilities and 1.28% of households held savings accounts. The study noted that several households held multiple credit and savings facilities; however, microfinance institutions are not the most common source of loans or savings for households in Kenya with other sources ranking higher. The other sources for loans include shopkeepers, mobile money and family/ friends/ neighbours while other modes of savings include mobile money, group savings and secret hiding places. The majority of the households held one (1) credit facility and one (1) saving facility and 1.14% of the households that held loan facilities obtained these from microfinance institutions. Interestingly, the top reasons indicated by households for obtaining loans and for saving with microfinance institutions included education, making it one of the highest household costs in Kenya. The proportion of households that give salaries and guarantees to obtain loans for microfinance institutions is 7.5 and 31.3% respectively, which is unsurprising due to group lending. The average wealth of the households was 2.74 indicating that the majority of households are almost at middle income level. The study also clearly revealed that households that obtain loans from and save with microfinance institutions have a higher wealth index, at 3.5 and 3.8 respectively as compared to both households who obtain loans and save from other sources and those who do not borrow nor save. The latter had the lowest wealth index at 2.6 and 2.3, which indicates that they are somewhat poor. This confirms the overall outcome of this study and previous literature as it shows that when households borrow and save, their welfare improves. Three variables were chosen to assess household welfare: monthly household expenditure, monthly household income and the wealth index. All the regression models included both independent (access to MFI loans, amounts of MFI loans and savings by households with microfinance institutions) and control variables (age, gender, household size, marriage status, education level, household location) to analyse the impact on household welfare. The estimated results showed an overall increase in household welfare due to the usage of and access to MFI products in Kenya. Microfinance institutions have a positive impact at different levels of significance on the welfare indicators, i.e., monthly household expenditures, household incomes and the wealth index. However, the study also noted that household savings in microfinance institutions do not affect household incomes. The results also showed that most of the household characteristics (such as gender of the household head, education of the household head, age of the household head, location of household, size of household) influence welfare indicators. There are various recommendations proposed from the findings of this study. Firstly, the findings indicate that household characteristics play a very important role in access to and usage of microfinance products and services in Kenya and therefore should be a consideration for policymakers when designing and implementing policy interventions to improve financial access. Secondly, the study showed that microfinance institutions are not the most common source of loans or savings for households, with other sources ranking higher, which portends an issue for the continued viability of microfinance institutions and thus innovations in the industry will be critical to ensure continued relevance. Thirdly, usage of microfinance products and services is important to improve household welfare and therefore financial literacy of customers should be part of education curriculum as well as part of the training provided by microfinance institutions and other financial institutions to ensure positive outcomes and ensure repeat uptake of microfinance products and services. Lastly, it is important to ensure that all microfinance institutions operate in an appropriate regulatory environment to ensure that customers are well protected and data protection and privacy issues are well managed.